2022
DOI: 10.3389/fphar.2022.876235
|View full text |Cite
|
Sign up to set email alerts
|

Storax Inhibits Caveolae-Mediated Transcytosis at Blood-Brain Barrier After Ischemic Stroke in Rats

Abstract: Background and Purpose: Blood-brain barrier (BBB) disruption following ischemic stroke (IS) contributes to hemorrhagic transformation, brain edema, increased neural dysfunction, secondary injury, and mortality. The prevailing view attributes the destruction of tight junction proteins (TJs) to the resulting BBB damage following IS. However, recent studies define a stepwise impairment of the transcellular barrier followed by the paracellular barrier which accounts for the BBB leakage in IS. The increased endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It has been postulated that Mfsd2a may serve to modulate transcytotic mechanisms in CNS endothelial cells for therapeutic purposes [ 66 ]. Recent research confirmed that storax attenuated BBB disruption by upregulating Mfsd2a and inhibiting Cav-1 in the endothelial cells in order to arrest the progression of cerebral ischemia [ 67 ]. Similarly, treatment with LPC-DHA, transported through Mfsd2a, strongly improved retinal function in 5xFAD mice [ 68 ], and treatment with fish oil significantly increased Mfsd2a expression and blood vessel coverage in the retinas of wild-type mice [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that Mfsd2a may serve to modulate transcytotic mechanisms in CNS endothelial cells for therapeutic purposes [ 66 ]. Recent research confirmed that storax attenuated BBB disruption by upregulating Mfsd2a and inhibiting Cav-1 in the endothelial cells in order to arrest the progression of cerebral ischemia [ 67 ]. Similarly, treatment with LPC-DHA, transported through Mfsd2a, strongly improved retinal function in 5xFAD mice [ 68 ], and treatment with fish oil significantly increased Mfsd2a expression and blood vessel coverage in the retinas of wild-type mice [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33,38] Styrax treatment inhibits caveolaemediated transcytosis at BBB in the focal stroke model of rats. [39] Besides modulating BBB permeability, other mechanisms include modulating inflammatory responses, regulating central excitatory and inhibitory neurons and neurotransmitters, [40,41] improving local microcirculation, and enhancing cerebral metabolism. [42]…”
Section: The Mechanisms Of Aromatic Herbsmentioning
confidence: 99%
“…Furthermore, styrax treatment after focal ischemic stroke improves long-term neurological outcomes, reduces cerebral infarct volume, and inhibits caveolae-mediated transcytosis in the blood-brain barrier (Zhou et al. 2021 , 2022 ). However, the exact mechanisms underlying the cerebral protective effects of styrax at the metabolite level are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%